Estudo fisiológico de Desmodesmus spinosus exposta ao cobre na presença e ausência de bactérias - Oliveira, Tamires de Freitas (2018)
Copper enters water bodies through physical and chemical processes, thus ensuring their presence in aquatic environments. In addition, it can be dumped in significant amounts by industrial, agricultural and mining activities, generating residues potentially toxic to aquatic biota. Copper is an essential micronutrient for microalgae and acts in biochemical processes that are fundamental to maintaining their life. However, when in concentrations above those usually experienced by these organisms, copper may have toxic effects and, as a consequence, induce biochemical changes in algal biomass. This study aimed at investigating the effects bacteria community on copper toxicity to the microalgae Desmodesmus spinosus and its interference in metabolic processes such as the synthesis and accumulation of biomolecules. This research was divided into two parts. In the first one we exposed axenic cultures of D. spinosus to several copper concentrations in order to define one concentration to be tested in the presence of bacteria, the second part. Growth parameters, biomolecules and photosynthetic activity of the microalga were evaluated in both the absence and presence of bacteria. Our objective in the first part was to select a copper concentration that affected the general microalgae metabolism but did not cause its death. For the first part copper concentrations ranged from 0.007 to 3.5 μM and the results showed that 3.5 μM Cu2+ inhibited the growth and photosynthetic activity of the microalga, while increasing the carbohydrate concentration. Microalga / bacterial interactions are complex and can influence the interpretation of what occurs in the environment and in laboratory tests. In this research, we conclude that the presence of bacteria can alter the toxicity of copper to microalgae. In part 2, the presence of bacteria stimulated the growth of microalgae, while kept equal to the synthesis and accumulation of chlorophyll and formed up to 8 cenobia cells, which had not been detected in axenic cultures. In addition, in the presence of bacteria, 3x more carbohydrates were accumulated in the algal biomass. We showed that D. spinosus is a copper-resistant microalgae and can therefore be indicated in bioremediation processes of environments contaminated with this element.